Factors Affecting Transfer Pricing - Umi Kalsum; Rika Henda Safitri; Mukhtaruddin Mukhtaruddin; Riska Novelia (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to examine the factors that influence transfer pricing including profitability, bonus mechanism, exchange rate, company size, debt covenant, tunneling incentive, intangible assets, tax minimisation, tax haven, audit committee, independent commissioner, managerial ownership and institutional ownership. The population of this study consists of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. The data sample was collected using purposive sampling technique and resulted in 60 observation data. The results of the analysis show that the variables of profitability (X1), bonus mechanism (X2), company size (X4), audit committee (X10), independent commissioner (X11), institutional ownership (X12) have an effect on transfer pricing, while the exchange rate (X3), debt covenant (X5), tunneling incentive (X6), intangible assets (X7), tax minimization (X8), tax haven (X9), and managerial ownership (X13) have no effect on transfer pricing.